Pharmacological and low-level laser therapy in radiation-induced oral mucositis in patients with head and neck cancer - Wicaksono, Imme Kris; Hapid, M. Hasan; Dewi, Tenny Setiani; Sufiawati, Irna; Kusumadjati, Adji (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: Oral mucositis (OM) is common in people undergoing radiotherapy, chemotherapy, or a combination of both. Pharmacological and low-level laser therapy (LLLT) are potential treatments to reduce pain and accelerate the healing process. Purpose: The aim of this case report is to describe the effectiveness of combining pharmacological therapy and LLLT for OM. Case: A 54-year-old man with post-hemi glossectomy diagnosed with tongue cancer was referred from the radio-oncology department with complaints of painful sores all over the oral cavity after receiving radiotherapy. The canker sores worsened when eating but felt more comfortable when drinking cold water. Intraoral examination revealed erythematous lesions accompanied by fibrinous pseudomembranes and yellowish-white plaques, which could be scraped off, leaving erythematous areas with pain. These lesions were present on the upper and lower labial mucosa and the right and left buccal mucosa. The diagnosis was grade-3 OM, according to the World Health Organization (WHO) criteria. Case management: Pharmacological therapy included 0.025% hyaluronic acid gargles three times a day and the use of LLLT with a wavelength of 976 nm. Conclusion: The combination of pharmacological therapy with LLLT was effective in maintaining and improving the condition of the oral mucosa by reducing pain and ultimately improving the patient’s quality of life.